Research on endogenous security data sharing mechanism of F-RAN for 6G - Yang LIU; Jun LI; Wenyun CHEN; Mugen PENG (Tongxin xuebao)
In order to solve the data security problem of data sharing in the fog radio access network in the 6G mobile communication system, an endogenous secure data sharing mechanism that realized local differential privacy and dynamic batch auditing was proposed.First, the user ran the RAPPOR algorithm locally on the data to protect data privacy.Next, the fog access point cached and preprocessed the data.Then the high power node performed a data integrity audit based on the BLS signature and Merkle hash tree on the data cached on the fog access point.Finally, the BBU pool infered the original distribution of shared data through statistical analysis.Security analysis and simulation show that the proposed mechanism realizes the local differential privacy of users, supports secure multi-client batch audit and data dynamic operation, and has high efficiency in time, space and communication.